ABOUT IMPROVEMENT OF CORNEAL GRAFT PRESERVATION BY USING REGULATORY PEPTIDES - S. A. Borzenok; O. I. Rolik; N. A. Onischenko; Y. A. Komakh (Вестник трансплантологии и искусственных органов)
It was analyzed traditional and modern types of cadaveric donor corneas preservation for penetrating kerato- plasty, descemet stripping endothelial keratoplasty and descemet membrane endothelial keratoplasty. It was described the possibility of corneal damage decreasing and increasing of efficient corneal endothelia cells pre- serving by using regulatory peptides into preserving medium. It was emphasized the main role of peptide drugs as new generation revitalizers for preserving viability of endothelial cells.